Monitoring and Modeling of Saline-Sodic Vertisol Reclamation by Echinochloa stagnina - Maman Nassirou Ado; Didier Michot; Yadji Guero; Zahra Thomas; Christian Walter (Soil Systems, 2022)
Soil salinity due to irrigation is a major constraint to agriculture, particularly in arid and semi-arid zones, due to water scarcity and high evaporation rates. Reducing salinity is a fundamental objective for protecting the soil and supporting agricultural production. The present study aimed to empirically measure and simulate with a model, the reduction in soil salinity in a Vertisol by the cultivation and irrigation of Echinochloa stagnina. Laboratory soil column experiments were conducted to test three treatments: (i) ponded bare soil without crops, (ii) ponded soil cultivated with E. stagnina in two successive cropping seasons and (iii) ponded soil permanently cultivated with E. stagnina with a staggered harvest. After 11 months of E. stagnina growth, the electrical conductivity of soil saturated paste (ECe) decreased by 79–88% in the topsoil layer (0–8 cm) in both soils cultivated with E. stagnina and in bare soil. In contrast, in the deepest soil layer (18–25 cm), the ECe decreased more in soil cultivated with E. stagnina (41–83%) than in bare soil (32–58%). Salt stocks, which were initially similar in the columns, decreased more in soil cultivated with E. stagnina (65–87%) than in bare soil (34–45%). The simulation model Hydrus-1D was used to predict the general trends in soil salinity and compare them to measurements. Both the measurements and model predictions highlighted the contrast between the two cropping seasons: soil salinity decreased slowly during the first cropping season and rapidly during the second cropping season following the intercropping season. Our results also suggested that planting E. stagnina was a promising option for controlling the salinity of saline-sodic Vertisols.